PERSEPSI MASYARAKAT TENTANG GADAI EMAS DI PEGADAIAN SYARIAH CABANG SETIA BUDI MEDAN - Meilinda Sari; Ilyda Sudardjat (Ekonomi dan Keuangan, 2013)
The title of this the public perception about pawning gold of Pegadaian Syariah Cabang Setia Budi Medan. The purpose of the research is to determine the extent to which understanding of the public about process of pawning gold to give by Pegadaian Syariah. The data used in this research are primary data and secondary data. The collecting of the primary data is done by giving the questionnaire to the customer of Pegadaian Syariah, while the secondary data are obtained from Pegadaian Syariah, books, literature, internet and others. The analysis method that used in this research is descriptive analysis using SPSS 16,0 version. The result of this research understanding customer’s or community about pawning gold is various. No one understands anyone not understands. But my observation, that has become a permanent customer’s of Pegadaian Syariah understanding about pawning gold to given and they have opinion about how to pawn gold of Pegadaian Syariah very easy and not many requirements. Keywords : Perception, Understanding, Pawning Gold